The gateway bug to edible insect consumption: interactions between message framing, celebrity endorsement and online social support - Legendre, Tiffany S; Baker, Melissa A (International journal of contemporary hospitality management, 2021)
Purpose Climate change and global population growth are threatening the sustainability of hospitality food systems. Foodservice organizations are seeking an optimal solution for this problem. The United Nations Food and Agriculture Organization proposed edible insects as a solution, yet the “yuck” factor discourages consumers from actively endorsing this option. Thus, this study aims to find ways to increase consumer acceptance of edible insects. Design/methodology/approach A 2 (message framing: hedonic vs utilitarian) × 2 (celebrity endorsement: absence vs presence) × 2 (social support: low vs high) between-subjects factorial design experiment was conducted. Findings The significant three-way interaction effects show that when celebrity endorsement is absent, there is no difference in restaurant advocacy (RA) and experience satisfaction between utilitarian and hedonic message framing, regardless of low (vs high) social support. However, when celebrity endorsement is present and social support is not lacking, a hedonic (vs a utilitarian) message had more significant effects on dependent variables. Conversely, when celebrity-endorsed messages receive high social support, utilitarian (vs hedonic) messages had a more substantial effect on the outcome variables. Originality/value This study contributes to alternative protein and associated consumer psychology and hospitality marketing literature by introducing marketing strategies for edible insects. By demonstrating the three-way interaction effects of message framing, celebrity, endorsement and social support on RA and experience satisfaction, this study could demonstrate some boundary conditions to consider when applying celebrity endorsement strategies (e.g. message framing and social support). Also, by addressing the effects of social support, this study builds upon the lack of hospitality literature on online social support.